Community-Based Counterterrorism - Spalek, Basia; Weeks, Douglas (Taylor and Francis Group, 2017)
Fifteen years of intensive studies following 11 September 2001 (9/11) has advanced many aspects of academic knowledge and practitioner practices within the counterterrorism domain. On a collective basis, both strands continue to advance understanding, application and capability. However, despite those advances, the threat of violent extremism remains high with little sign of abatement. Moreover, since 9/11 governments around the globe are increasingly focusing on the threat within. Seemingly not a day passes where there is not some mention in the media of the internal threat posed by radicalization, returning foreign fighters, someone arrested on suspicion of a terror attack, or an actual attack. Constrained by legal frameworks, governments are increasingly looking to partner with communities in their counterterrorism efforts. This special edition highlights some of those efforts and gives insight to some of the ways that is occurring.